If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 + 6x + 6 = 52 Reorder the terms: 3 + 6 + 4x + 6x = 52 Combine like terms: 3 + 6 = 9 9 + 4x + 6x = 52 Combine like terms: 4x + 6x = 10x 9 + 10x = 52 Solving 9 + 10x = 52 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 10x = 52 + -9 Combine like terms: 9 + -9 = 0 0 + 10x = 52 + -9 10x = 52 + -9 Combine like terms: 52 + -9 = 43 10x = 43 Divide each side by '10'. x = 4.3 Simplifying x = 4.3
| -5+6x-12y=24 | | 2x^2-13=10x | | -t=-2-10 | | inx+in(x-6)=in(2x) | | 8x-58=2*2+34 | | 8=8(1-6k) | | 1h=1 | | 6x+4x+6+4=38 | | -9+6w=5w | | a^2+1=29 | | 3(5y+2)-y=u+8 | | -92=4(-7x-2) | | 5x+55=9x-9 | | 2(3a+9)=20 | | 26p-4-11p=15p+6 | | 8x-4=4x+44 | | -6(4x+7)=78 | | -7p-39=5(-5p+3) | | -8(2x-2)=128 | | -14+4x-2x=30 | | P=A-ArT | | X^2+4y^2+6x+16y=11 | | 3x^26y-24=0 | | 10(9-x)= | | 35-(2c+3)=2(c-6)+c | | -7p-39=5(-5p+30) | | 3y+6x=360 | | 10x^2-17x+34=7x^2-26x+28 | | -15+-14e=-33 | | -13-8j=-5 | | 9m+6=96# | | 4b+6=-22 |